Laparoscopic Radical Trachelectomy for Embryonal Rhabdomyosarcoma of the Cervix in a 2-Year-Old Girl. Issue 6 (December 2018) - May, Taymaa; Allen, Lisa; Hogen, Liat; King, Carol; Lorenzo, Armando J.; Browne-Farmer, Chantelle; Gupta, Abha; Shaikh, Furqan
Abstract : BACKGROUND: Embryonal rhabdomyosarcoma of the cervix is a rare and aggressive malignancy that usually affects children and young adults. CASE: We describe a 2-year-old patient who presented with a mass protruding through the vaginal introitus. Preoperative investigations including vaginoscopy, hysteroscopy, magnetic resonance imaging, and biopsies confirmed embryonal rhabdomyosarcoma, botryoid subtype, arising from the cervix. She was successfully treated with neoadjuvant chemotherapy and interval laparoscopic radical trachelectomy to achieve remission. CONCLUSION: Collaboration between the pediatric and adult surgical and medical oncology teams was critical to implement this fertility-sparing treatment strategy in such a young girl having this rare tumor. Abstract : Fertility-preserving radical trachelectomy preceded by neoadjuvant chemotherapy was a successful treatment strategy for a 2-year-old girl with embryonal rhabdomyosarcoma of the cervix.